“But What Should I Do in my Methodology Chapter?” Promoting Philosophy as Legitimate Educational Research - Norris, Trevor (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
In this paper, I argue that the dominant assumption that educational research means empirical research narrows the range of possibilities for educational research. More specifically, research methods courses and textbooks exclude philosophy of education as a viable way of going about educational research, which limits what we can know about education by predetermining what counts as a legitimate way of doing educational research. My concern is that the assumption that educational research is limited to qualitative, quantitative, or mixed-methods research marginalizes other ways of knowing. I begin by exploring the problem of “tacit empiricism,” the assumption that educational research means empirical research, which I explore in several educational research methods textbooks and course syllabi. I then critique some underlying epistemological assumptions in empirical research, and lament that the proliferation of qualitative methods has not translated into the inclusion of philosophy as a legitimate way to do educational research. I suggest that the requirement that educational research have a practical “impact,” based on a limited notion of what counts as “evidence,” is a key reason why philosophy of education is marginalized. This leads to a consideration of the often-overlooked AERA “Standards for Reporting on Humanities-Oriented Research,” which can help promote philosophical research when it comes to evaluating submissions to educational journals or conferences. I then argue that it is important to rethink the word “research” itself so that it includes reading, writing and thinking. In conclusion, I suggest a few practical ways in which philosophy of education can be promoted in the face of these challenges.